Pengaruh Green Accounting terhadap Kepedulian Lingkungan Pengusaha UMKM Laundry di Kecamatan Sukolilo - Pramesti, Astri Ayu; Dewi, Nadia Fransiska; Novita, Febriantri; Pandin, Maria Yovita R (Journal of Multidiscipline and Collaboration Research, 2024)
This research aims to evaluate the knowledge and practice of implementing the green accounting concept among laundry business owners in Sukolilo sub-district. The method used is descriptive analysis, focusing on laundry owners as the research object. The results of the tests carried out by researchers using SPSS v 26, T test showed that environmental concern was 0.057 < 0.05 so it could be proven that environmental concern had a significant effect on cost knowledge. Environmental awareness is 0.161 > 0.05 so it can be proven that environmental awareness has a significant effect on cost knowledge. The F Test results also show that Environmental Concern and Awareness jointly influence Cost Knowledge. And the R test shows that the independent variable, namely environmental concern and awareness, contributes an influence of 5.1 percent to the level of the dependent variable, namely cost knowledge. This indicates that it can be concluded that laundry business owners in Sukolilo sub-district quite understand and apply the concept of green accounting in their business.